PENGARUH KESEHATAN KESELAMATAN KERJA DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (Studi Kasus Pada Karyawan bagian Produksi Pabrik Kelapa Sawit PTPN V Unit Lubuk Dalam, Kabupaten Siak) - Rara Dinara Putri; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research is motivated by the importance of human resources in a company to be able to produce quality products amid business competition in the globalization era. Human resources are an important role for the success of the PTPN V palm oil mill company Lubuk Dalam unit, Siak Regency because humans are living assets that need to be maintained and developed. To increase work productivity company employees must pay attention to what factors serve as a support in influencing work productivity. This research was conducted at the PTPN V palm oil mill company Lubuk Dalam unit, Siak Regency. The purpose of this study was to determine the level of Employee Production Prooductivity at the PTPN V Oil Palm Plant in Lubuk Dalam unit, Siak Regency. The sample of this study was taken as many as 104 respondents but due to the impact of Covid19, the researchers only obtained 60 respondents using the sampling method. In this research the method used is descriptive and quantitative. Data obtained from interviews and questionnaires / questionnaires were then tested with statistics through the SPSS program. The analytical method used in this study is simple and multiple regression analysis, and by passing the validity test and the reliability test. In this study the results obtained were that Occupational Safety and Health (K3) had a positive and significant effect on Work Productivity, Work Discipline had a positive and significant effect on Work Productivity, and Occupational Safety and Health (K3) and Work Discipline had a positive and significant effect on Employee Productivity. at the Palm Oil Mill PTPN V Lubuk Dalam unit, Siak Regency.Keywords: Occupational Safety Health (K3), Discipline Work, Productivity Work